The Excited Helium Photoionization - O, Lhagva; S, Danzan (Scientific transaction of the National University of Mongolia. Physics, 2022)
The photoionization characteristic behaviour of the excited He atom has been studied by using the parametrical approach, and the physical nature of the processes is cleared up. It is shown that in the excited He photoionization, the profiles of the resonance structures appear far enough from the positions of autoionization states at energies comparable hundred times of their natural widths. The mentioned peculiarities in the recombination of the He+ ioninto excited states have been observed too. It is also shown that such "extended" resonance structures are well described by "width" and "profile" functions of the energy.The competition and interference of phototransitions to open and closed (autoionization resonance) channels are found to be due to the broadening and shift in the resonance structure profile formed in the photoprocesses with the excited He. The ways to revealexperimentally the influence of closed channels in the resonance structure forming the photoprocesses with excited He atoms are discussed.